2016
DOI: 10.1038/srep27072
|View full text |Cite
|
Sign up to set email alerts
|

A 3D in vitro model to explore the inter-conversion between epithelial and mesenchymal states during EMT and its reversion

Abstract: Epithelial-to-mesenchymal transitions (EMT) are strongly implicated in cancer dissemination. Intermediate states, arising from inter-conversion between epithelial (E) and mesenchymal (M) states, are characterized by phenotypic heterogeneity combining E and M features and increased plasticity. Hybrid EMT states are highly relevant in metastatic contexts, but have been largely neglected, partially due to the lack of physiologically-relevant 3D platforms to study them. Here we propose a new in vitro model, combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 64 publications
4
67
0
1
Order By: Relevance
“…Spheroid cultures are considered to be better suited for studying a wide range of cellular activities, such as tissue development and disease. [9][10][11] MET is an essential initiation step in stem cell reprogramming and thus dedifferentiation of mesenchymal lineage cell types. It has been reported that cancer cell spheroids mimic a more "realistic" cellular response to radioactive [4] and chemical [5] treatments than cancer cells maintained as 2-dimensional (2D) monolayer culture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spheroid cultures are considered to be better suited for studying a wide range of cellular activities, such as tissue development and disease. [9][10][11] MET is an essential initiation step in stem cell reprogramming and thus dedifferentiation of mesenchymal lineage cell types. It has been reported that cancer cell spheroids mimic a more "realistic" cellular response to radioactive [4] and chemical [5] treatments than cancer cells maintained as 2-dimensional (2D) monolayer culture.…”
mentioning
confidence: 99%
“…These genes relate to cell differentiation and cell reprogramming, particularly key pluripotency genes Oct4, Sox2, and Nanog. [9][10][11] MET is an essential initiation step in stem cell reprogramming and thus dedifferentiation of mesenchymal lineage cell types. [9] Research has also revealed that spheroid cultures favors mesenchymal-to-epithelial transition (MET), maintenance and even induction of epithelial phenotypes in various cell types.…”
mentioning
confidence: 99%
“…With regard to the design of a successor of the aging collagen gel assay, we can focus on biomaterials that will encourage epithelial migration and EMT-stimulated morphological changes and invasion (Gill et al, 2012;Bidarra et al, 2016). As the natural extracellular microenvironment is a highly hydrated network, artificial hydrogels are the material of choice.…”
Section: A Hydrogel Platform To Stimulate In Vivo Emt Processesmentioning
confidence: 99%
“…1) (Gill et al, 2012;Weiss et al, 2012;O'Connor et al, 2015;Wei et al, 2015;Bidarra et al, 2016). 1) (Gill et al, 2012;Weiss et al, 2012;O'Connor et al, 2015;Wei et al, 2015;Bidarra et al, 2016).…”
Section: A Hydrogel Platform To Stimulate In Vivo Emt Processesunclassified
“…Among scaffolds culturing the use of alginate, a polymer obtained from brown algae, has been widely applied for 3D cancer cell culturing [21,22] and to cancer stem-cell [23,24]. Additionally, alginate has intrinsic biocompatibility and capacity for forming gel with well-defined features, such as size and density [25] and moreover, it mimics the extracellular matrix or basal membrane to support cell functions and metabolism [26].…”
Section: Introductionmentioning
confidence: 99%